Molecular analysis of endometrial inflammation in preterm birth - Cecati, M.; Sartini, D.; Campagna, R.; Biagini, A.; Ciavattini, A.; Emanuelli, M.; Giannubilo, S. R. (Cellular and Molecular Biology, 2017)
Spontaneous preterm birth (sPTB) represents the 35%–45% of all preterm birth (PTB) cases and its etiology is unknown. We investigated if the expression level of endometrial cytokines and angiogenetic factors is related to the onset of sPTB.Endometrial tissues from non-pregnant women who experienced sPTB and from non-pregnant women who did not experience sPTB were collected and examined for their expression profile. With this aim, the PCR Array analysis was performed and data were confirmed by Real-Time PCR. Differential gene expression measurements (pathological vs control tissues) showed a significant up-regulation for genes codifying for two angiogenetic factors known as connective tissue growth factor (CTGF), and coagulation factor III (F3). An increased level of expression was detected both for tyrosine kinase endothelial (TEK) and for transforming growth factor beta 2 (TGF-Î²2) genes but without reaching the statistical significance. The expression level of interleukin 10 receptor alpha (IL10RA) gene was slightly decreased in pathological group compared to control one but, as well as forTEK and TGF-Î²2 measurements, without reaching the statistical significance. Our work is the first to correlate the imbalance in endometrial district of non -pregnant women with sPTB. These data could suggest a new point of view whence to read sPTB. We need additional clinical and biological studies to clarify sPTB pathogenesis.